2010
DOI: 10.1061/(asce)co.1943-7862.0000153
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study of the Risks and Difficulties in Implementing Guaranteed Maximum Price and Target Cost Contracts in Construction

Abstract: Over the past few decades, both the guaranteed maximum price (GMP) and target cost contracting (TCC) arrangements have been regarded as alternative integrated procurement strategies for clients to mitigate risks, minimize claims, integrate the diverse interests of a complex construction project and offer incentives to provide value-added services. However, the adoption of GMP/TCC contracts may also generate significant risks and difficulties that merit considerable attention. This paper aims to provide a conci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 13 publications
3
15
0
3
Order By: Relevance
“…A profound look at literature studies shows that there is dearth of literature focusing on employees' perspective of incentive programs and its effects on their safety behavior and performance [ 33 ]. Moreover, past studies have provided evidence from industrialized countries, e.g., China, UK, USA [ 34 ], or rapidly developing countries, e.g., India [ 29 ], but safety literature from developing economics is scarce and limited [ 1 ]. Furthermore, the results offered by past studies on effectiveness of I/P programs are also mixed and contradictory [ 21 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…A profound look at literature studies shows that there is dearth of literature focusing on employees' perspective of incentive programs and its effects on their safety behavior and performance [ 33 ]. Moreover, past studies have provided evidence from industrialized countries, e.g., China, UK, USA [ 34 ], or rapidly developing countries, e.g., India [ 29 ], but safety literature from developing economics is scarce and limited [ 1 ]. Furthermore, the results offered by past studies on effectiveness of I/P programs are also mixed and contradictory [ 21 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The subject of risk management in construction projects has been increasingly studying since the 1980s. Most of these studies have focused on how risks are identified or analyzed/assessed in different countries such as Australia [32,33], China [23,34,35], Ghana [36], Hong Kong [37,38], India [39,40], Indonesia [41,42], Italy [43], Korea [44], Malaysia [31,45], Mexico [46], New Zealand [47,48], Nigeria [49,50], Poland [51], Singapore [52,53], Spain [54], Sri Lanka [55], Tanzania [56], the United Kingdom [57,58], the United States of America [59,60], Vietnam [61,62] and Zambia [63]. These studies mostly used survey/interviews or case studies.…”
Section: Introductionmentioning
confidence: 99%
“…γ) προτάσεις υπολογισμού του ύψους των κινήτρων και προσδιορισμού συνοδευόμενων κινδύνων (Ward & Chapman, 1995;Jafaari, 1996;Al-Subhi Al-Harbi, 1998;Arditi & Yasamis, 1998;Berends, 2000;Broome & Perry, 2002;Shr & Chen, 2003;Olsen & Osmundsen, 2005;Chan et al, 2010;Hosseinian & Carmichael, 2013και Boukendour & Hughes, 2014.…”
Section: στόχος και σημασία της παρούσας έρευναςunclassified
“…Συχνότερη είναι η περίπτωση κινήτρου για μείωση του κόστους όπου ορίζεται το κόστος -στόχος του έργου και σε περίπτωση μικρότερου τελικού κόστους, ο ανάδοχος και η ΑΑ μοιράζουν το κέρδος, η οποία ονομάζεται στη βιβλιογραφία και ως «Target Cost Contract», σύμβαση προϋπολογισμού στόχου (Broome & Perry, 2002;Chan et al, 2010). Υπάρχει και η παραλλαγή κατά την οποία ο κατασκευαστής εγγυάται ότι το συνολικό κόστος του έργου δεν θα ξεπεράσει κάποιο ποσό αναλαμβάνοντας όλο το επιπλέον κόστος (Veld & Peeters, 1989).…”
Section: κόστος συν κίνητρο (κσκ)unclassified
See 1 more Smart Citation